Major Economic Tendencies in the Bituminous Coal Industry - Veenstra, Theodore A.; Fritz, Wilbert G. (Quarterly Journal of Economics, 1936)
The problem of overcapacity, 106.— Trends in production and consumption, 112.— Mechanization, 117.— Labor problems, 122.— Wages, 127.— Summary, 128.